Catching-up effects in the logistics industry and the dynamic linkages with international trade and economic growth: empirical evidence from an international panel dataset - Katrakylidis, Ioannis; Madas, Michael (Economics and Business Letters, 2020)
We analyze the dynamic linkages among Logistics, Trade and Economic Growth for a panel of 39 countries over the period 2007-2018. In particular, we investigate whether these countries exhibit the tendency to catch up, in terms of logistics performance, with the leader country, using methodologies of “convergence analysis” appropriate for the notions of stochastic convergence and β-convergence and perform Granger-causality tests among a catching up variable (the LPI of each country relative to the LPI of Germany), Trade Openness and economic growth. The findings reveal rather weak evidence of catching-up effects with Germany. As far as causality is concerned, trade and economic growth further enhance the global tendency in logistics performance to catch-up with the dominant Germany while convergence in logistics is found to directly support economic growth but not trade.